Innate Immune Responses in Children and Adults with Shigellosis - Raqib, Rubhana (American Society for Microbiology, 2000)
An array of pro- and anti-inflammatory mediators of the innate immune system was analyzed in stool, urine, and rectal mucosa samples from adults and children with shigellosis to better understand their role in recovery from and in the immunopathogenesis of the disease. Increased concentrations of lactoferrin (Lf), myeloperoxidase (MPO), prostaglandin E(2), and leukotriene B(4) (LTB(4)) in stool during acute shigellosis in both children and adults indicated that activated cells of the innate defense system at the mucosal site were secreting the mediators. Increased concentration of MPO and 8-iso-prostaglandin F(2α) and lower levels of superoxide dismutase (SOD) activity in stool during acute Shigella infection suggested increased formation of reactive oxygen species, free radical-catalyzed peroxidation of membrane lipids, and decreased scavenging of the reactive oxygen radicals. In children, lower expression of SOD in tissue with severe inflammation and lower levels of SOD activity in stool for longer periods compared to adults may further worsen the tissue damage and predispose the children to a lowered defense. Both adult and pediatric patients had significantly higher expression of inducible nitric oxide synthase (iNOS) in the rectum with severe inflammation, compared to that seen with mild inflammation, accompanied by persistently up-regulated iNOS mRNA, reflecting increased production of nitric oxide at the local site. However, in contrast to adults, reduced urinary nitrate levels in pediatric patients during acute shigellosis suggested lower production of nitric oxide in the renal compartment. Persistent production of Lf in pediatric patients may contribute to chronic inflammation in the rectum. In addition, increased production of proinflammatory mediators in the rectum of patients with severe histology suggested contribution of these molecules to the immunopathogenesis of severe colitis caused by shigellae.